Efficacy of websites as a communication tool for Chilean deputies. - Fuente-Alba Cariola, Fernando (2019)
This article studies the effectiveness of websites of Chilean deputies as a communication tool. Researchers conduct a content analysis of the entire website of parliamentarians at two moments: 2015 and 2018. A first fact is that only half of the deputies have a website, rejecting its potential as a communication tool for citizens. In addition, none of the 129 websites analyzed, 66 in 2015 and 63 in 2018, is effective in terms of digital communication, underutilizing the informative and dialogical potential of this tool. The article also provides information about the use of Facebook and Twitter by parliamentarians. In the light of the results, the websites of Chilean deputies are used in the old logic of mass communication that includes a sender and a passive public, contradicting the digital democratization that characterizes the communication of the 21st century.